2018
DOI: 10.1111/pai.12962
|View full text |Cite
|
Sign up to set email alerts
|

Clinically diagnosed urticaria and risk of systemic lupus erythematosus in children: A nationwide population‐based case‐control study

Abstract: Our results suggest that children with urticaria have a significantly higher risk of SLE, with the risk increasing further among those with more episodes of urticaria or chronic urticaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…The logistic regression analysis of 2000–2011 claims data from the Taiwanese National Health Insurance Research Database of 2105 children suffering from SLE. It is indicated that there is an increased risk of developing acute urticaria and CU, particularly in female patients [48 ]. A comprehensive literature review indicated that chronic hepatitis B and C are not associated with CSU and so routine screening for these viral infections in CSU patients is not necessary [49 ].…”
Section: Multimorbiditiesmentioning
confidence: 99%
“…The logistic regression analysis of 2000–2011 claims data from the Taiwanese National Health Insurance Research Database of 2105 children suffering from SLE. It is indicated that there is an increased risk of developing acute urticaria and CU, particularly in female patients [48 ]. A comprehensive literature review indicated that chronic hepatitis B and C are not associated with CSU and so routine screening for these viral infections in CSU patients is not necessary [49 ].…”
Section: Multimorbiditiesmentioning
confidence: 99%
“…After the first round of title and abstract review, 19 051 articles were excluded as they obviously did not meet the eligibility criteria based on study design and type of article, leaving 63 articles for full‐length article review. A total of 55 articles were excluded at this stage as the outcome of interest was not reported, leaving eight articles 12‐19 with 3 326 171 participants for the meta‐analysis. Literature review and study selection process are summarized in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Five of 8 included studies 12‐16 relied on patients’ self‐report of AR through direct interviews or health questionnaires rather than physician diagnosis to ascertain AR. In addition, 3 studies 17‐19 relied on diagnostic codes for ascertainment of AR and SLE. Therefore, the accuracy of diagnoses and comprehensiveness of case identification could be limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 15 16 17 18 ] There are also studies to suggest the association between AD and SLE although the results are still conflicting. [ 19 20 21 22 23 24 25 26 ] This systematic review and meta-analysis was performed in order to comprehensively investigate the relationship between AD and SLE by identifying all relevant studies and summarizing their results together.…”
Section: Introductionmentioning
confidence: 99%